HIV-related stigma in pregnancy and early postpartum of mothers living with HIV in Ontario, Canada. Issue 2 (1st February 2017) - Ion, Allyson; Wagner, Anne C.; Greene, Saara; Loutfy, Mona R.
ABSTRACT: HIV-related stigma is associated with many psychological challenges; however, minimal research has explored how perceived HIV-related stigma intersects with psychosocial issues that mothers living with HIV may experience including depression, perceived stress and social isolation. The present study aims to describe the correlates and predictors of HIV-related stigma in a cohort of women living with HIV (WLWH) from across Ontario, Canada during pregnancy and early postpartum. From March 2011 to December 2012, WLWH ≥ 18 years ( n  = 77) completed a study instrument measuring independent variables including sociodemographic characteristics, perceived stress, depression symptoms, social isolation, social support and perceived racism in the third trimester and 3, 6 and 12 months postpartum. Multivariable linear regression was employed to explore the relationship between HIV-related stigma and multiple independent variables. HIV-related stigma generally increased from pregnancy to postpartum; however, there were no significant differences in HIV-related stigma across all study time points. In multivariable regression, depression symptoms and perceived racism were significant predictors of overall HIV-related stigma from pregnancy to postpartum. The present analysis contributes to our understanding of HIV-related stigma throughout the pregnancy–motherhood trajectory for WLWH including the interactional relationship between HIV-related stigma and other psychosocial variables, most notably, depression and racism.